Utilization of Barcode Scanning Media to Optimize Technology-based Science Learning for Elementary School Students - Precilia, Riska; Utami, Ratnasari Diah (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to reveal the use of barcode scan media as an effort to optimize technology-based science learning and obtain student learning outcomes in science subjects that can be operated on devices with the Android system. Methodology: The method used is descriptive analytical using a qualitative approach. Data collection methods in this study include observation, interviews, and documentation. Observations were conducted at SD Muhammadiyah PK Baturan, especially class 5 with a total of 25 students. The validity of the data to be used in this study is source triangulation and tech-nique triangulation. Data analysis in this case organizes, sorts, groups, codes and categorizes the collected data, both from the field, images, and documents in the form of reports. Results: The results of the study show that technology-based barcode scanning learning media is very good so that it can be used by students to support learning activities because students are more motivated to learn. Applications/Originality/Value: The findings of this study can be used as a reference for teachers in teaching students to use learning media to optimize student learning outcomes.